Open Shoulder Stabilization for Anterior Glenohumeral Instability: The Latarjet Procedure - Jesse H. Morris MD; Gustavo A. Barrazueta MD; Gregory L. Cvetanovich MD (SAGE Publishing, 2022)
Background: Traumatic anterior glenohumeral instability is a commonly encountered shoulder pathology among young active patients. Nonoperative management and arthroscopic techniques are associated with high rates of reoccurrence, particularly in patient populations with known major risk factors. Indications: The coracoid process transfer (Latarjet procedure) is typically reserved for cases of anterior glenohumeral instability where glenoid deficiency exceeds 20% to 25% or when soft tissue stabilization techniques have failed. Technique Description: We use a standard open deltopectoral approach. The coracoid process is exposed and released from the pectoralis minor and coracoacromial ligament. An osteotomy is performed using an oscillating saw and completed with an osteotome to harvest the bone block, leaving the conjoint tendon intact. Soft tissue is cleared from the graft, and it is predrilled/measured. We use a subscapularis splitting technique to access the joint and expose the anterior glenoid. All bony surfaces are prepared. We drill into the glenoid at the premeasured offset. The graft is provisionally fixed into place with K wires, then secured with 2 parallel cannulated screws. The capsule is repaired to make the graft extraarticular. The subscapularis split is repaired in addition to standard closure. Results: The Latarjet procedure is very successful for restoring stability. Rates of recurrent dislocation range from 0% to 10% across various studies, and revision rates are as small as 3%. This is much lower than those seen following soft tissue stabilization, particularly in high-risk patient populations. Patient reported outcomes show good function and high rates of return to sport. Complication rates are generally higher, with some studies reporting up to 25% incidence. Musculocutaneous and axillary nerve injuries may occur, and graft overhang can lead to glenohumeral arthritis. Certain complications are unique to the procedure, including graft lysis, coracoid fracture, nonunion, and hardware issues. Discussion/Conclusion: The Latarjet procedure is very useful in cases of anterior glenohumeral instability with significant glenoid bone loss or following failed soft tissue stabilization. Its utilization may continue to grow in future years as technique innovations develop and surgical indications expand.